PREVENTIF KPID DKI MENGURANGI DAMPAK PERKEMBANGAN MEDIA MASSA MELALUI SOSIALISASI LITERASI MEDIA TERHADAP MAHASISWA DI JAKARTA - Nieke Monika Kulsum (Universitas Nasional, 2016)
This research based on the statement of the Indonesian Commission of Education stating as much as 62.7 percent of teenagers in Indonesia ever do relationship as husband and wife. Supported data from the BKKBN stating that 51 percent of teens have been doing free sex. In addition, drug users at the time of the teen aged 12-21 years old in 2013 its about 14,000people from the number of teens in Indonesia around 70 million people and from BNN release that since 2003 drug transactions are increased as much as 300 percent from 2010. This problem does not yet include a brawl between students, murder, and other negative cases among youth. Allegedly, the mass media are one of the causes for this to happen. In an effort to prevent the negative impact of mass media, are currently evolving thoughts about medialiteracy. That aims to control the interests and influence of mass media in the lives of individuals, families and communities as well as helping to design actions in handling the influence. Where users have media literacy media will attempt to give a reaction and assess media messages something with full awareness and responsibility. One of the institutions that concern to this is KPI (Indonesia Broadcasting Commission Area). Where in order to stem theimpact of mass media against young people is to hold a workshop or training on the media literacy of the students in Jakarta.